Low-voltage bridge strategy to guide cryoablation of typical and atypical atrioventricular nodal re-entry tachycardia in children: mid-term outcomes in a large cohort of patients. Issue 2 (10th October 2020) - Drago, Fabrizio; Calvieri, Camilla; Russo, Mario Salvatore; Remoli, Romolo; Pazzano, Vincenzo; Battipaglia, Irma; Gimigliano, Fabrizio; Allegretti, Greta; Silvetti, Massimo Stefano
Abstract: Aims: In the current literature, results of the low-voltage bridge (LVB) ablation strategy for the definitive treatment of atrioventricular nodal re-entry tachycardia (AVNRT) seem to be encouraging also in children. The aims of this study were (i) to prospectively evaluate the mid-term efficacy of LVB ablation in a very large cohort of children with AVNRT, and (ii) to identify electrophysiological factors associated with recurrence. Methods and results: One hundred and eighty-four children (42% male, mean age 13 ± 4 years) with AVNRT underwent transcatheter cryoablation guided by voltage mapping of the Koch's triangle. Acute procedural success was 99.2% in children showing AVNRT inducibility at the electrophysiological study. The overall recurrence rate was 2.7%. The presence of two LVBs, a longer fluoroscopy time and the presence of both typical and atypical AVNRT, were found to be significantly associated with an increased recurrence rate during mid-term follow-up. Conversely, there was no significant association between recurrences and patient's age, type of LVB, lesion length, number of cryolesions or catheter tip size. Conclusion: The LVB ablation strategy is very effective in AVNRT treatment in children. Recurrences are related to the complexity of the arrhythmogenic substrate.